2021
DOI: 10.31244/jero.2021.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Besteht ein Zusammenhang zwischen dem Besuch eines inklusiven Bildungssettings und dem Selbstwertgefühl von Schüler:innen ohne sonderpädagogischen Förderbedarf?

Abstract: Vergleiche in sozialen Interaktionen sind zentral für das individuelle Selbstwertgefühl. Inwiefern heterogene Bezugsgruppen hinsichtlich sozialen und ethnischen, aber auch körperlichen, geistigen und kognitiven Merkmalen und Voraussetzungen, wie sie nicht erst seit Ratifizierung der UN-Behindertenrechtskonvention in Klassen des allgemeinen Bildungssystems zu finden sind, das Selbstwertgefühl bedingen, ist noch unzureichend beantwortet. Qualitative Studien zeigen bislang, dass Schüler:innen ohne sonderpädagogis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Studies based on data from NEPS SC3 investigated the effects of inclusive class composition (proportion of students with special educational needs) and found that students without special educational needs reported lower self-esteem in inclusive classes than peers in noninclusive classes. However, this association can be traced back to socioeconomic class composition and course of education (Labsch et al, 2021). In addition, changing schools or experiencing a class repetition may be critical events during one's educational career that also affect one's own learning environment.…”
Section: (4) Reuse Potentialmentioning
confidence: 99%
“…Studies based on data from NEPS SC3 investigated the effects of inclusive class composition (proportion of students with special educational needs) and found that students without special educational needs reported lower self-esteem in inclusive classes than peers in noninclusive classes. However, this association can be traced back to socioeconomic class composition and course of education (Labsch et al, 2021). In addition, changing schools or experiencing a class repetition may be critical events during one's educational career that also affect one's own learning environment.…”
Section: (4) Reuse Potentialmentioning
confidence: 99%